Analysis of the Financial Statements of the Langkat Provincial Government Based on PP No. 8 of 2006 - Prayoga, Rizky Ananda; Siregar , Saparuddin; Nasution, Yenni Samri Juliati (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the compliance of the Langkat District Government's financial statements with Government Regulation Number 8 of 2006 concerning Financial Reporting and Performance of Government Agencies, and identify challenges in their preparation. The research method used was qualitative with data collection through observation, interviews with three informants, and documentation. The results showed that the financial statements of the Langkat District Government had complied with Government Regulation No. 8 of 2006 which requires transparency, accountability, and compliance with Government Accounting Standards (SAP). Challenges identified include limited understanding of SAP, differences in interpretation of regulations, and limited competent human resources, which have an impact on the quality of financial statements. This research contributes to the field of public sector accounting by highlighting the challenges and compliance in financial reporting at local government institutions.